Most Individuals With Advanced Cirrhosis Have Sleep Disturbances, Which are Associated with Poor Quality of Life - Ghabril, Marwan (Clin Gastroenterol Hepatol, 2017)
BACKGROUND & AIMS: Sleep disturbances are common in patients with cirrhosis, but their determinants and effects on health-related quality of life are not well understood. We investigated the prevalence of disturbed sleep in these patients, factors associated with sleep disruption, and effects on quality of life. METHODS: We performed a prospective, cross-sectional study of 193 stable ambulatory patients with cirrhosis (154 with decompensated cirrhosis). Participants completed the Pittsburgh sleep questionnaire index (to assess sleep quality), the chronic liver disease questionnaire (CLDQ), muscle cramp questionnaires, and underwent neurocognitive testing. Actigraphy was performed in a subset of patients with normal and disturbed sleep. We collected serum samples from subjects with normal and disturbed sleep and performed non-targeted metabolomic analyses. RESULTS: Of the study subjects, 157 (81%) had disturbed sleep, with Pittsburgh sleep questionnaire index scores >5. Disturbed sleep was associated with muscle cramps, daytime somnolence, and decreased quality of life, based on CLDQ scores. Factors independently associated with disturbed sleep in logistic regression analysis included hypoalbuminemia, opiate therapy, and muscle cramps. Disturbed sleep was independently associated with CLDQ score (correlation parameter, −36.6; 95% CI, −24 to −49; P<.001) on linear regression. Disturbed sleep was associated with neurocognitive impairment and with significantly delayed bedtime and decreased total sleep time, measured by actigraphy. Disturbed sleep was associated with metabolome signatures of alterations to the intestinal microbiome and lipid, arginine, and urea cycle metabolism. CONCLUSION: Most patients (81%) with advanced cirrhosis have disturbed sleep. This has negative effects on quality of life and is associated with disruptions of several metabolic pathways, including metabolism by the intestinal microbiota.